ASSESSMENT OF FUNDING MODELS FOR EFFECTIVE MANAGEMENT OF PRIVATE UNIVERSITIES IN ENUGU STATE (Scientific Journal of Educational Management, Research and law, 2025)
The study assessed the funding models for effective management of private universities in Enugu State. Two research questions guided the study while two hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population for the study was 102 which comprised 43 management staff and 59 finance officers. Census sampling technique was employed because the population was manageable. The instrument for data collection was a researcher structured 12-item questionnaire titled “Funding Models for Effective Management of Private Universities Questionnaire (FMEMPUQ)”. The instrument was validated by three experts. Cronbach alpha statistic was used to determine the reliability and it has an overall reliability index of .81. Mean and standard deviations were used to answer the research questions while t-test statistic was used to test the null hypotheses. The findings of the study showed that tuition fees and donations from alumni are important funding models that contribute to effective management of private universities in Enugu State to a high extent. In view of the findings, the researcher recommended that Private universities in Enugu State should implement robust systems for efficient collection and management of tuition fees to ensure consistent financial stability and operational effectiveness.